Clinical Characteristics and Pharmacological Treatment of Individuals With and Without Intellectual Disability in Pre-trial Assessment—A Population-Based Study - Edberg, Hanna; Chen, Qi; Andiné, Peter; Larsson, Henrik; Hirvikoski, Tatja (Frontiers in Psychiatry, 2020)
Background The current lack of knowledge about intellectual disability (ID) in forensic psychiatric contexts can compromise the legal certainty of these individuals during the medico-legal process. To address ambiguous results in previous literature, the aim of the current study was to estimate the prevalence of ID in a pre-trial forensic psychiatric settings. Moreover, as little is known about the characteristics of offenders with ID, we conducted a clinical characterization of individuals with and without ID being subject to forensic psychiatric assessment. Methods Using data from several Swedish national registers, we conducted a population-based retrospective observational study on 8442 individuals being subject to pre-trial forensic psychiatric assessments in Sweden in 1997-2013. We performed univariate analyses to compare the characteristics of individuals with (n = 537) and without ID (n = 7905). Results The prevalence of ID was 6.4% in the Swedish pre-trial forensic psychiatric context during the observational period. Compared with individuals without ID, individuals with ID were younger at the time of assessment, had a lower educational level, and had less frequently started families. ID was associated with lower frequency of diagnosed psychotic and bipolar disorders. However, a similar prescription rate of antipsychotics, and a comparable rate of previous inpatient care was observed among individuals with and without ID. Individuals with ID had more often been prescribed anti-libidinal treatments often used for treating sexual disorders, although did not present a higher prevalence of sexual disorder. Conclusions The prevalence of ID among pre-trial individuals being subject to forensic psychiatric assessment was more than twice as high as assumed in the general population. Our results suggest that individuals with ID received pharmacotherapy without clear indication. Remaining challenges in the clinical management of individuals with ID were indicated by the discrepancy between the occurrence of psychiatric diagnoses, pharmacological treatment patterns, and rates of inpatient care.